Comrades betrayed: Jewish World War I veterans under Hitler - Geheran, Michael (Battlegrounds: Cornell studies in military history, 2020)
"Jewish veterans developed a distinctive manner of thinking and behaving as a consequence of their World War I experience, socialization in the military, and status. They embraced specific ideologies of masculinity to counter Nazi antisemitic stereotypes"--